IMPACT OF DISRUPTION ON SUSTAINABLE MANAGEMENT PRACTICES IN AFRICA: ANALYZING CRITICAL ISSUES AND EVALUATING STRATEGIC CHOICES FOR THE FUTURE. (Journal of the Management Sciences, 2024)
Africa's journey towards sustainable management practices is marked by a dynamic interplay of disruptive forces that present both challenges and opportunities. This study explores the multifaceted impacts of disruption on sustainability in Africa, considering factors such as technological advancements, climate change, geopolitical shifts, demographic dynamics, and global health crises. Through the lens of resilience theory, this examination provides insights into how complex systems respond to disruptions and adapt to change, offering a valuable framework for guiding sustainable practices. The challenges faced by Africa are diverse, including issues related to technology, environmental concerns, and healthcare vulnerabilities. However, these challenges also bring opportunities for innovation, green initiatives, and economic growth. Informed decision-making, collaboration, and resilience are essential as Africa shapes its path to sustainability. The decisions made today will influence future generations, making it crucial for policymakers, businesses, civil society, and individuals to make informed choices, develop resilient strategies, and contribute to a more sustainable and inclusive future for the continent. This comprehensive assessment serves as a reference point and an inspiration for collective action and collaboration, fostering a more sustainable and prosperous future for Africa.
Keywords: Disruption, Sustainable Management, Strategic Choices, Africa.